Damage evolution mechanism and low-damage grinding technology of silicon carbide ceramics - Chen Li; Kechong Wang; Oleg Zakharov; Hailong Cui; Mingtao Wu; Tianchen Zhao; Yongda Yan; Yanquan Geng (International Journal of Extreme Manufacturing)
Silicon carbide (SiC) ceramics are extensively utilized in aerospace, national defense, and petrochemical industries due to their superior physical and chemical properties. The processing of bulk SiC ceramics necessitates precise and efficient grinding techniques to produce components with satisfactory functionality. However, the inherent high hardness and brittleness of SiC ceramics present significant challenges during grinding, leading to severe brittle fracture and tool wear that compromise both surface integrity and production efficiency. Although ductile-regime grinding of SiC ceramics can be achieved by enhancing machine tool accuracy and stiffness while optimizing wheel performance alongside appropriate selection of process parameters, a comprehensive summary of the mechanisms underlying damage evolution during grinding is lacking, and a mature grinding process for SiC ceramics has yet to be developed. To bridge this gap, the sintering technologies, mechanical properties, and microstructures of SiC ceramics were briefly covered. The grinding-induced damage mechanism and low-damage grinding technologies of SiC ceramics were summarized. The fundamental science underlying the ductile deformation and removal mechanisms of brittle solids was emphasized. Additionally, attention was directed towards the critical role of hybrid energy field grinding in minimizing brittle damages and promoting removal efficiency. This review not only elucidates the intrinsic interactions between the work material and abrasives, but also offers valuable insights for optimizing the grinding processes of brittle solids.